2019
DOI: 10.1074/jbc.ra119.007947
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic and heterotypic trans-assembly of human Rab-family small GTPases in reconstituted membrane tethering

Abstract: Membrane tethering is a highly regulated event occurring during the initial physical contact between membrane-bounded transport carriers and their target subcellular membrane compartments, thereby ensuring the spatiotemporal specificity of intracellular membrane trafficking. Although Rab-family small GTPases and specific Rab-interacting effectors, such as coiledcoil tethering proteins and multisubunit tethering complexes, are known to be involved in membrane tethering, how these protein components directly act… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(70 citation statements)
references
References 44 publications
3
67
0
Order By: Relevance
“…LC3B‐His12 and GATE‐16‐His12 proteins triggered efficient tethering of synthetic, but physiologically mimicking, DOGS‐NTA‐bearing liposomes (100 nm in diameter; Figure a) even at the protein‐to‐lipid molar ratios of 1:1,000 or below (black and blue circles, respectively, in Figure b). However, Rab5a‐His12, which has been so far found to be the most active membrane tether among human Rab‐family small GTPase isoforms, had the substantially less tethering capacity under the same conditions (green circles, Figure b) and, H‐Ras‐His12, used as the negative control of a C‐terminally His12‐tagged protein, was completely unable to initiate liposome tethering in the turbidity assays (cyan circles, Figure b). Moreover, the kinetic liposome turbidity assays indicated that the initial velocities of human LC3B‐ and GATE‐16‐mediated membrane tethering reactions were much higher than that of the Rab5a‐mediated reaction, when tested at the protein‐to‐lipid ratios of 1:500 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…LC3B‐His12 and GATE‐16‐His12 proteins triggered efficient tethering of synthetic, but physiologically mimicking, DOGS‐NTA‐bearing liposomes (100 nm in diameter; Figure a) even at the protein‐to‐lipid molar ratios of 1:1,000 or below (black and blue circles, respectively, in Figure b). However, Rab5a‐His12, which has been so far found to be the most active membrane tether among human Rab‐family small GTPase isoforms, had the substantially less tethering capacity under the same conditions (green circles, Figure b) and, H‐Ras‐His12, used as the negative control of a C‐terminally His12‐tagged protein, was completely unable to initiate liposome tethering in the turbidity assays (cyan circles, Figure b). Moreover, the kinetic liposome turbidity assays indicated that the initial velocities of human LC3B‐ and GATE‐16‐mediated membrane tethering reactions were much higher than that of the Rab5a‐mediated reaction, when tested at the protein‐to‐lipid ratios of 1:500 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…To comprehensively and quantitatively evaluate the intrinsic membrane tethering capacities of human LC3B and GATE‐16 proteins in a chemically defined proteoliposomal system, we employed three types of reconstituted liposome tethering assays, which had been previously developed to test membrane tethering driven by human Rab‐family small GTPases in our recent studies, including a high‐throughput 384‐well microplate‐based endpoint assay to measure the turbidity of liposomes (Figure b), a kinetic assay to monitor liposome turbidity changes (Figure c), and a fluorescence cell counter‐based imaging assay giving an unbiased quantitative data of clusters of tethered liposomes (Figure d,e). Strikingly, both of the human Atg8 proteins exhibited the abilities to drive highly efficient and rapid membrane tethering by themselves, in the absence of any other additional protein components (Figure b–e).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations